2012
DOI: 10.1021/es301758c
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-Mediated Modulation of Steroidogenic Gene Expression in Hypoxic Zebrafish Embryos: Implications for the Disruption of Sex Steroids

Abstract: Hypoxia can impair reproduction of fishes through the disruption of sex steroids. Here, using zebrafish (Danio rerio) embryos, we investigated (i) whether hypoxia can directly affect steroidogenesis independent of pituitary regulation via modulation of steroidogenic gene expression, and (ii) the role of leptin in hypoxia-induced disruption of steroidogenesis. Exposure of fertilized zebrafish embryos to hypoxia (1.0 mg O(2) L(-1)) from 0-72 h postfertilization (hpf), a developmental window when steroidogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Our study showed the same mortality rate (50%) at 5 mM and 10 mM concentrations, although the concentrations we used were higher than those used by Reinardy et al At this mortality rate, we conducted our study of residual live larvae. Kajimura and Yu used the concentrations of CoCl 2 used in the present study to induce HIF-1α expression [ 58 , 59 ]. Therefore, our strategy for collecting live larvae and measuring the expression of neovascularization-related genes such as vegfaa and vegfr2 in CoCl 2 -treated embryos is reasonable, although the expression level of vegf may come from extra-ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the same mortality rate (50%) at 5 mM and 10 mM concentrations, although the concentrations we used were higher than those used by Reinardy et al At this mortality rate, we conducted our study of residual live larvae. Kajimura and Yu used the concentrations of CoCl 2 used in the present study to induce HIF-1α expression [ 58 , 59 ]. Therefore, our strategy for collecting live larvae and measuring the expression of neovascularization-related genes such as vegfaa and vegfr2 in CoCl 2 -treated embryos is reasonable, although the expression level of vegf may come from extra-ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…increases hepatic lep mRNA expression in fish (Chu et al 2010, Yu et al 2012. Given the anorexigenic effects of leptin in rainbow trout (Murashita et al 2008, Aguilar et al 2010, the inverse relationship between hepatic lep-a1 mRNA expression and food intake in C. salmositica-infected fish and the increase in plasma leptin-A1 levels during acute infection suggest that leptin contributes to the regulation of food intake at peak parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vivo studies have shown that fish reproduction is affected by hypoxia via alteration of the steroidogenesis pathway 711. Steroid hormones biosynthesis is a fundamental process for reproduction in vertebrates, and all steroid hormones are derived from cholesterol.…”
Section: Introductionmentioning
confidence: 99%